Expression, purification, crystallization and preliminary X‐ray crystallographic study of the nucleocapsid protein of Tomato spotted wilt virus. Issue 6 (31st May 2013) - Komoda, Keisuke; Narita, Masanori; Tanaka, Isao; Yao, Min
<x xml:space="preserve">Abstract</x> Tomato spotted wilt virus (TSWV), which causes severe damage to various agricultural crops such as tomato, pepper, lettuce and peanut, is a negative‐stranded RNA virus belonging to the Tospovirus genus of the Bunyaviridae family. Viral genomic RNA molecules are packaged in the form of ribonucleoprotein complexes, each of which contains one viral RNA molecule that is coated with many nucleocapsid (N) proteins. Here, the expression and crystallization of TSWV N protein are reported. Native and selenomethionine‐substituted crystals of N protein belonged to the same space group P21. Their unit‐cell parameters were a = 66.8, b = 97.2, c = 72.0 Å, β = 112.8° and a = 66.5, b = 96.3, c = 72.1 Å, β = 113.4°, respectively.